Model Edukasi dalam Mengenali Tanda Bahaya Kehamilan pada Ibu Hamil - Silvia Saputri; Asya Nawar Karimah; Nur Samsiah; Lisa Trina Arlym (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Maternal mortality in Indonesia remains high, with one of the main contributing factors being delays in recognizing and responding to pregnancy danger signs. Appropriate and effective health education can improve pregnant women’s knowledge and preparedness regarding pregnancy risks. This study aims to systematically review educational models used to increase pregnant women’s awareness of pregnancy danger signs. The research method applied a Systematic Literature Review (SLR) approach based on the PICOS framework (Population: pregnant women, Intervention: educational models on pregnancy danger signs, Comparison: no intervention or standard education, Outcome: increased knowledge/preparedness, Study design: quantitative/intervention studies). Articles were retrieved from PubMed, ProQuest, SpringerLink, and ScienceDirect databases, published between June 2021 and 2025. After the selection and screening process, seven articles met the inclusion criteria. All articles were evaluated using the Critical Appraisal Skills Programme (CASP) to assess methodological quality and validity. The results showed that community-based education, mHealth interventions, and social norm–based approaches were effective in improving pregnant women’s knowledge of pregnancy danger signs. This study recommends integrating community-based and technology-based educational approaches while considering the local context to enhance program effectiveness